The Spread of Technology through Commercial Networks in the Nineteenth Century:Foreign Merchant-entrepreneurs and Calabrian Sericulture amid Changes and Conflicts - Fusco, Idamaria (The Historical Review/La Revue Historique, 2011)
No abstract